Malaysian Youth’s Quality of Life: Looking from the Perspective of Eating Behaviour - Delicious, Dynatalie; Chik, Chemah Tamby; Jipiu, Lovelyna Benedict (Jurnal Gizi dan Pangan, 2025)
The purpose of this study is to identify the relationship between eating behaviour and quality of life among youth in Malaysia. The systematic literature review and thematic content analysis initiated in Scopus, Web of Science, Science Direct, and PubMed published from 2018 to 2022 were reviewed. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards were followed for conducting the systematic review. A set of inclusion and exclusion criteria was used to identify relevant research, and data extraction and analysis were done to investigate the relationships. The study quality was assessed using the "Quality Assessment Tool for Quantitative Studies". The systematic result found 8 studies classified as eligible (cross-sectional) out of 111 articles reviewed which looked at the relationship between eating behaviour and quality of life, while also emphasizing the lack of research that the topic being studied. This study highlighted unhealthy eating behaviour and dietary patterns associated with lower quality of life. Furthermore, the importance of promoting public awareness about eating healthy and nutrition knowledge was highlighted in this study. Information obtained from this research will benefit the individuals, researchers, institutions, and community to advance knowledge and future practice.